The gasolinazo (gasoline price hike) and the agricultural sector: a case study of the effects on the competitiveness of the guava (Psidium guajava L.) in Aguascalientes - Borja Bravo, Mercedes; García Salazar, José Alberto; Almeraya Quintero, Xochilt; Cuevas Reyes, Venancio (Acta Universitaria, 2019)
The aim was to determine the effect of the increase in the price of the gasoline on the profitability and competitiveness of guava cultivation in Aguascalientes and the effects that the government policy will have on this activity. Using the Policy Analysis Matrix, the behavior of indicators in three scenarios with different fuel prices, compared to a baseline scenario, was analyzed. It was found that the private gain of producers decreased 12.9%, the private cost ratio increased from 0.48 to 0.51, and there was a loss of competitiveness in the production of guava before the price of gasoline in 2017. The cost of this policy represents a tax higher than 4% on the income of the producer. It is concluded that the increase in the price of gasoline will have a negative impact on competitiveness and will exacerbate the lack of public policy on guava production in Aguascalientes.